Immunogenicity and antitumor activity of the superlytic λF7 phage nanoparticles displaying a HER2/neu-derived peptide AE37 in a tumor model of BALB/c mice. (28th June 2018) - Barati, Nastaran; Razazan, Atefeh; Nicastro, Jessica; Slavcev, Roderick; Arab, Atefeh; Mosaffa, Fatemeh; Nikpoor, Amin Reza; Badiee, Ali; Jaafari, Mahmoud Reza; Behravan, Javad
Abstract: Phage display technique has been increasingly researched for vaccine design and delivery strategies in recent years. In this study, the AE37 (Ii-Key/HER-2/neu 776–790) peptide derived from HER2 (human epidermal growth factor receptor protein) was used as a fused peptide to the lambda phage (λF7) coat protein gpD, and the phage nanoparticles were used to induce antitumor immunogenicity in a TUBO model of breast cancer in mice. Mice were immunized with the AE37 peptide displaying phage, λF7 (gpD::AE37) every 2-week intervals over 6-weeks, then the generated immune responses were evaluated. An induction of CTL immune response by the λF7 (gpD::AE37) construct compared to the control λF7 and buffer groups was observed in vitro . Moreover, in the in vivo studies, the vaccine candidate showed promising prophylactic and therapeutic effects against the HER2 overexpressing cancer in BALB/c mice. Highlights: Bacteriophage λ displaying the HER2/neu derived peptide AE37. Immunological studies on TUBO cancer cell line and mice bearing HER2+breast cancer. Prophylactic and therapeutic studies on mice bearing HER2 + breast cancer.